Il terzo occhio. Alcune ipotesi sul pensiero filosofico tardo - Paternoster, Alfredo (Elephant & Castle, 2018)
In this article, I try to apply the concept of late style to the philosophical work, specifically to analytic philosophy. My analysis is based on a single case-study, the late work of Hilary Putnam. I show that the most relevant features of late style, as they have been individuated by Edward W. Said (in the wake of Theodor W. Adorno), can be only partially applied to the philosophical work taken into consideration. Yet, I propose that other different characters of Putnam’s late work could arguably be regarded as expressing a late style, more distinctively philosophical. Eventually, I raise some doubts concerning the concept of late style in general.